Interactive multiobjective fuzzy random linear programming: Maximization of possibility and probability - Katagiri, Hideki; Sakawa, Masatoshi; Kato, Kosuke; Nishizaki, Ichiro (European journal of operational research, 2008)
This paper considers multiobjective linear programming problems with fuzzy random variables coefficients. A new decision making model is proposed to maximize both possibility and probability, which is based on possibilistic programming and stochastic programming. An interactive algorithm is constructed to obtain a satisficing solution satisfying at least weak Pareto optimality.